A Sustainable Ecology Movemen - Wigke Capri Arti (PCD Journal, 2020)
This article examines and discusses a sustainable ecology movement that has protested the mangan mine in Manggarai, East Nusa Tenggara, since 2000. This movement has united Catholicism and indigenous religion in an effort to promote sustainability, conservation, and environmentalism. Using the institutions of tradition and religion, this movement has negotiated with the State and the private sector and advocated for a moratorium in mining. This article is a qualitative one, employing interviews and focus group discussions as well as a review of documents and previous research into Manggarai and mining conducted by the Research Centre for Politics and Government (PolGov). This study seeks to understand how tradition and religion have been consolidated in their efforts to stop mining in Manggarai. It makes four important findings. First, although manganese does not have much economic value, it is important for poor provinces such as East Nusa Tenggara. Second, Catholicism and indigenous religion have united to advocate for ecological sustainability and oppose manganese mining. Third, traditional and Catholic institutions have strengthened the bonds between members. Fourth, in a literature dominated by studies of religious movements and extractivism, this article contributes a fresh perspective on extractivism and political ecology.